Chronic Bullous Disease of Childhood with IgG Predominance: What is the Locus Standi? - Haneef, Nayeem Sadath (Medknow Publications & Media Pvt Ltd, 2012)
Linear IgA disease (LAD) is an acquired, autoimmune, subepidermal, blistering disease, characterized by linear deposition of IgA along the dermoepidermal junction on immunofluorescence. Some cases known as ‘mixed immunobullous disease’ show weak staining with other immune reactants like IgG, IgM or C3. We report a rare case of a child having typical manifestations of LAD (chronic bullous disease of childhood), but with IgG predominance rather than IgA. Obviously it is improper to term this as linear IgA disease. Such cases are reported in literature as variants of LAD, with a multitude of terms like mixed immune bullous disease, linear IgG / IgA disease, linear IgA / IgG disease, and so on. In view of the tremendous confusion that these multiple terms cause in the absence of any practical benefit, we propose that the broad term ‘chronic bullous disease of childhood’ be applied to all childhood cases, irrespective of the nature of the immune deposits.